Authentic Leadership and its implications for Workplace Bullying: An Analytical study of the Opinions of a Ssmple of Individuals Working in Governmental Hospitals in Dohuk Governorate - Ali huseen, Kawar; Nori , Rang (Humanities Journal of University of Zakho, 2021)
The research deals with one of the contemporary issues in the organizational field, as authenticity is one of the most important foundations adopted by the leadership that has a positive impact on the subordinates and the organizational performance. The basic idea of ​​this study involves the reflection of the Authentic leadership dimensions of administrative leaders on bullying among individuals in the workplace in the Health sector. It aims to diagnose the dimensions of Authentic leadership and its impact on bullying, specifically in State hospitals in Dohuk Governorate in the Kurdistan Region-Iraq, the research population included individuals working in (10) governmental hospitals, which represent 80% of all governmental hospitals in Duhok city. To test research hypotheses, Questionnairen used as a main tool for collecting primary data. 230 of questionnaires were given to individuals working in the studied hospitals and only (197) valid questionnaires entered the process of data analysis. In order to reach the Research objectives and test its hypotheses, all data were analyzed using the SPSS 23. The study revealed that there is a significant correlation between the dimensions of the Authentic leadership which represented by Self-awareness, Balanced Processing, Internalized Moral Perspective, Relational Transparency and bullying in workplace. Hwoever, Balanced Processing and the Internalized Moral Perspective showed statisticaly significant impact on minimizing bullying in workplace, whereas both self-awareness and Relational transparency have not showon statisticaly significant impact on bullying in workplace. The study concluded with the necessity of more studying the literature by researchers and it need more investigating in future, as well as recommending future studies on developmental orientation.